Social Justice: An Outreach-extension Program - Lapiz, Gary B; Aranas, Amelia Girly L; Lagrosas, Anabelle C (ASEAN Journal of Community Engagement, 2021)
The impact of the COVID-19 pandemic on communities in the Philippines has affected in-person research on community engagement. This paper highlighted the necessity for continuous research on social justice during the pandemic in order to discover ways in which people can survive and thrive through the trying times. The paper is based on the extension program of the Cebu Normal University (CNU) Research Institute of Public Governance on Social Justice. It analyzed Kaangayan, the public education workshop on social justice’s report to the Office of Extension Services and International Linkages. The report is based on an outreach extension service conducted in a barangay (community) in Cebu, Philippines. The pure “fishbowls” qualitative research method was employed to conduct the analysis, and participants were selected through an open invitation that was extended to the barangay. Based on the concluded activity, the report was prepared and submitted to the Office of Extension Services and International Linkages. Subsequently, all data was consolidated, processed, saturated, and finalized toward the qualitative results on policy analysis based on the technical/completion of outreach extension project and the results of the technical evaluation.